The Error Analysis of Grammar Found in Students’ Writing on WhatsApp - Tri Jampi Setiyorini; Suwarna; Novi Lestari (Universitas Islam Negeri Palopo, 2025)
Grammar is a necessary language component to improve the proficiency of learner’ language. However, many secondary education learners still commit grammatical errors in typing their messages on WhatsApp. This research aims to describe grammatical errors types found in students’ writing on WhatsApp typed by 20 first-semester learners in an Indonesian university. The researchers used a descriptive case study to conduct the research. The research participants were 20 first-semester learners of a private university in Central Java, Indonesia. The researchers used a test to collect the data. They analyzed the tests results descriptively by using Keshavarz’s theory. The analysis result shows that the percentage for each error type is 27.5% (omission), 10.6% (addition), 58.2% (substitution), and 3.7% (permutation). The research result indicates that the most dominant error is substitution (58.2%).